AKAR PROBLEMATIK EKONOMI POLITIK PERTANIAN DAN UPAYA PENINGKATAN KESEJAHTERAAN PETANI - Didin S Damanhuri (Journal of Indonesian Economy and Business (JIEB), 2000)
During the first long term national development the government played the big role to control rice price in the market through the policy of floor and ceiling price. One of the most important reason is that rice has a high contribution to the growth of inflation. In fact the result of this study shows that during 1968 to 1996, the food group (that rice is included) has the lowest contribution to the growth inflation. Among 12 kinds of food in the food group the rice has the lowest contribution to inflation. Consequently, it is needed to improve the farmer welfare by improving rice price, rural industrialization, and erasing market distortion that empically caused the increasing of inflation rate.